2023
DOI: 10.3389/fepid.2023.1205857
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed hypertension and associated factors among adults in Durame town, Southern Ethiopia: a cross-sectional study

Abebe Suliman,
Sebsibe Tadesse,
Lonsako Abute
et al.

Abstract: BackgroundUndiagnosed hypertension is a major public health problem causing severe cardiovascular disorders that are responsible for a high proportion of morbidities and mortalities, especially among adults living in low-income countries. However, there is a paucity of information that describes its epidemiology in Ethiopia. This study aimed to assess the prevalence of undiagnosed hypertension and associated factors among adults in Durame town, southern Ethiopia.MethodsA community-based cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Physical inactivity was found in 62.5% of the participants in this study, which was higher than the results of the studies done in Durame town, Southern Ethiopia (36%) (24), Nigeria (30.7%) (28), Wolkait Tegedie Zone, Northwest Ethiopia (35.2%) [35], and physical inactivity was significantly associated with hypertension in all of these studies, including the current one. The higher prevalence of physical inactivity in the current study might partly explain the higher prevalence of hypertension in the present study as compared with most other studies.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Physical inactivity was found in 62.5% of the participants in this study, which was higher than the results of the studies done in Durame town, Southern Ethiopia (36%) (24), Nigeria (30.7%) (28), Wolkait Tegedie Zone, Northwest Ethiopia (35.2%) [35], and physical inactivity was significantly associated with hypertension in all of these studies, including the current one. The higher prevalence of physical inactivity in the current study might partly explain the higher prevalence of hypertension in the present study as compared with most other studies.…”
Section: Discussioncontrasting
confidence: 89%
“…The prevalence of newly diagnosed HTN (36.2%) in the present study is higher than the overall prevalence of hypertension reported from the national NCDs STEPS survey among the Ethiopian adult population (15.8%) [20], community-based cross-sectional studies in Addis Ababa, central Ethiopia (29.2%) [21], and Dire Dawa city, eastern Ethiopia (24.43%) [22], and a cross-sectional study on public health facilities in Addis Ababa, central Ethiopia (32.3%) [23]. It was also much higher than the prevalence of newly diagnosed HTN reported from studies done in Debre Markos town, north-west Ethiopia (12.7%) [24], Durame town, southern Ethiopia (14%) [25], and Gimbi Town, western Ethiopia (24.8%) [26]. The higher prevalence of undiagnosed HTN in the current study as compared with that of the overall prevalence of HTN in the national NCDs STEPS survey may be explained by the increasing burden of the predisposing factors for HTN.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to a study conducted in Durame town, Southern Ethiopia: family history of hypertension, drinking too much alcohol, physical inactivity, and low seeking healthcare for hypertensive symptoms without serious illness were significantly associated with developing undiagnosed hypertension. 23 Being older, overweight, and having a family history of hypertension is significantly associated with undiagnosed hypertension. 24 A study conducted in Mizan-Aman Town, Bench Sheko Zone, Southwest Ethiopia revealed that older age, being male, low physical activity, low consumption of fruits and vegetables, and higher body mass index (BMI) were significantly associated with undiagnosed hypertension.…”
Section: Introductionmentioning
confidence: 99%